EXPLORING WAYS IN WHICH GREENWEARFAIR CAN IMPROVE THEIR DIGITAL MARKETING - FATHAN KEVIN ALFPUTRA, MUHAMMAD
The world is experiencing a Covid-19 pandemic including Indonesia. The appeal to prevent the chain of spreading this virus requires people to stay at home. This has an impact on economic instability and one of those affected is Small and Medium Enterprises (SMEs) in fashion industry, which then requires fashion SMEs actors in Indonesia to be creative in marketing their products or services, one of which is through digital marketing. This research aims are to identify the things that need to be improved in Greenwearfair to reach enough customers and audiences using digital marketing, defining the effective ways to use digital marketing that need to be done, and to describe fashion SMEs in Indonesia using digital marketing to improve their marketing. This qualitative research uses literature study approach. The data collection technique used in this research is documentation in form of photos that describe the digital marketing activities carried out by Greenwearfair and also previous research journals published in 2020-2022 that analyze the use of digital marketing in SMEs actors in Indonesia obtained from Google Scholar and Science Direct. This research uses qualitative analysis technique with a deductive thinking approach. The findings of this research show that Greenwearfair has marketed its products using digital marketing through social media, including Instagram and TikTok. However, Greenwearfair must consistent in posting information about its products, both time consistency and quality of the postings; it should make post content more interesting by making testimonial videos from influencers to make the target audiences more interested in buying its products; and Greenwearfair should try to use other social media, such as YouTube, Facebook and WhatsApp to market its products, as well as cooperate with the leading Market Place in Indonesia, such as Tokopedia, Shopee, Bukalapak, Lazada, etc. to improve the quality of its digital marketing. Most fashion Industry SMEs in Indonesia use digital marketing, namely social media to market their products, while others use online advertising, email marketing, PPC marketing, SEO, and affiliate marketing to market their products. The top five social media rankings that are most often used by fashion SMEs actors in Indonesia during 2020-2022 are YouTube, WhatsApp, Facebook, TikTok, and Instagram. Other digital marketing media they used are Market Places (Tokopedia, Shopee, Bukalapak, Lazada, Blibli, etc.), Twitter, Web, FB Messenger, Line, WeChat, and Snapchat. They market their products by posting the pictures or videos, giving captions to each post, uploading statuses on social media, and interacting with audiences or customers by replying to their comments or questions.